Proposed physiological mechanisms of pranayama: A discussion - Samiran Mondal (Journal of Ayurveda and Integrative Medicine, 2024)
Background: Pranayama, or yogic breathing technique, is now well-known worldwide by ordinary people, doctors, and scientific communities for its immediate and long-term physiological effect. However, no comprehensive physiological mechanisms explained pranayama. The present study proposed these physiological mechanisms to interpret the underlying science behind pranayama. Method: The author searches PubMed/Medline internet sources for authentic scientific data and articles to acquire evidence following specific keywords. The author reviewed a total of seventy-three papers, following PRISMA guidelines. 17 full articles, including seven systematic reviews, five clinical trials, two observational studies, and three randomized control trials, have been selected to discuss proposed physiological mechanisms. Discussion: This study proposes physiological mechanisms of pranayama. It is commenced from Step 1. Activation of mechanoreceptors and chemoreceptors in the respiratory system; then Step 2. Activation of mechanoreceptors and chemoreceptors in the circulatory system, followed by Step 3. Activation of brain respiro-circulatory control centre; Step 4. Activation of the cerebellum; Step 5. Activation of the limbic system and finally end with; Step 6. Activation of the cerebral cortex. The physiological adjustment and adaptation mechanisms due to pranayama of all these six proposed areas have been discussed. Authentic scientific evidence has also been presented to support these proposed physiological mechanisms of pranayama. The author stated the study's limitations and suggested future specific scientific experiments in this area of proposed physiological mechanisms of pranayama. Conclusion: These prospective proposed physiological mechanisms of pranayama in the future may provide the best scientific background for therapeutic rehabilitation and for the healthy population to maintain their general wellness.